2014
DOI: 10.1017/s1478951514001126
|View full text |Cite
|
Sign up to set email alerts
|

Exploring traditional end-of-life beliefs, values, expectations, and practices among Chinese women living in England: Informing culturally safe care

Abstract: End-of-life discussions can be part of an arduous, painful, and uncomfortable process, particularly for migrants living on the margins of society in a new cultural setting. For some Chinese people living in the United Kingdom, end-of-life care requires attention to acculturation, particularly Western versus Eastern beliefs on religion, spirituality, burial practices, and provision of care, and the availability of culturally specific care, all of which encompass issues related to gender. Stories of a purposive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Within the Chinese culture, the teachings of Taoism, Confucianism, and Buddhism are coalesced with Chinese medicine, providing an alternate and at times contrasting approach to death and dying which may need to be addressed and potentially integrated into the care plan of members from these communities [ 42 , 43 ]. Although there is general agreement within the Chinese culture that life and death are a natural part of the human lifespan, the possibility of ‘a good death’ is highly influenced by their religious, spiritual and philosophical beliefs [ 1 ]. A further example of the influence of cultural and spiritual beliefs on death and dying was reported in a study on Hmong people, who reflect a syncretic spiritually, combining animism with more formal faith traditions such as Christianity [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the Chinese culture, the teachings of Taoism, Confucianism, and Buddhism are coalesced with Chinese medicine, providing an alternate and at times contrasting approach to death and dying which may need to be addressed and potentially integrated into the care plan of members from these communities [ 42 , 43 ]. Although there is general agreement within the Chinese culture that life and death are a natural part of the human lifespan, the possibility of ‘a good death’ is highly influenced by their religious, spiritual and philosophical beliefs [ 1 ]. A further example of the influence of cultural and spiritual beliefs on death and dying was reported in a study on Hmong people, who reflect a syncretic spiritually, combining animism with more formal faith traditions such as Christianity [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research reveals that family members from cultures that revere filial piety have significant influence on the dying wishes of the individual in terms of treatment options as well as religious and spiritual needs [ 1 , 9 ]. For example, within Chinese cultures, Confucianism and filial piety are values which are integral to family structures and relationships [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coward, Stajduhar, andBramadat (2012, 2013) edited two books on what a 'good death' looks like in different religious and spiritual traditions. In a systematic literature review of culturally-and spiritually-sensitive End-of-Life care (EoL), Fang et al (2015) reported numerous barriers, including under-utilization of culturally-sensitive models designed to improve EoL care; language barriers; lack of awareness of cultural and religious diversity issues; exclusion of families in the decision-making process; racial and religious discrimination; and lack of culturally-tailored EoL information to facilitate decision-making. Another body of literature related to religious diversity in home health, apart from palliative care, speaks to the role of faith and faith communities in providing social support, meaning and resilience (Gerdner, Tripp-Reimer, & Simpson 2007;Taylor, 2008;Walsh, 2014).…”
Section: Religious and Ethnic Diversity In Home Healthmentioning
confidence: 99%
“…A common misconception is that EA seniors require less care than other seniors due to traditional beliefs, values, and practices associated with filial piety whereby family members are expected to provide care and support (Fang, Malcoe, Sixsmith, Wong, & Callender, 2015).…”
mentioning
confidence: 99%